2007
DOI: 10.1097/sla.0b013e31814855f2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Surgical Outcomes as Measured by the American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP)

Abstract: Our data suggests higher rates of postsurgical morbidity and mortality related to the time of the year. Further study is needed to fully describe the etiologies of the seasonal variation in outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 32 publications
5
103
0
2
Order By: Relevance
“…22 There are also data from medical as well as other surgical specialties-some of which have been extracted from NSQIP-in which investigators found higher mortality rates in July. 2,3,5,6,18 Although our results do not agree with those of studies focusing on other specialties, our results are consistent with the findings of most other studies that have sought to determine whether a July Effect exists in the practice of neurosurgery. 4,14,15,20 These findings notwithstanding, in our clinical experience we have observed that the July transition period is fraught with clinical challenges.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…22 There are also data from medical as well as other surgical specialties-some of which have been extracted from NSQIP-in which investigators found higher mortality rates in July. 2,3,5,6,18 Although our results do not agree with those of studies focusing on other specialties, our results are consistent with the findings of most other studies that have sought to determine whether a July Effect exists in the practice of neurosurgery. 4,14,15,20 These findings notwithstanding, in our clinical experience we have observed that the July transition period is fraught with clinical challenges.…”
Section: Discussionsupporting
confidence: 78%
“…Large studies in other surgical specialties have demonstrated an increase in adverse outcomes in the late summer, suggesting an association between this transition period and poorer patient care. 2,6,9,11,16,19 The data are conflicting, however, because other studies have not found evidence for this phenomenon. 22 Despite great interest in the subject, there has been limited investigation of the July Effect in the field of neurosurgery.…”
mentioning
confidence: 44%
“…An observational cohort study analyzing data from the American College of Surgeons-National Surgical Quality Improvement Program database (ACS-NSQIP) database on overall surgeries noted an 18% increase in post-operative morbidity in the July 1 to August 30 cohort (n=9,941) when compared to the April 15 to June 15 cohort (n=10,313) (P=0.0005). A 41% increase in mortality between patient populations depending on the time of year was also noted (P=0.005) (10). The etiologies for this seasonal variation in outcomes have been attributable to both changes in weather patterns and changes in house-staff.…”
Section: Introductionmentioning
confidence: 90%
“…Although there is some evidence in favour of this hypothesis, [3][4][5][6] most studies, including those from medical, 7-9 surgical, 10-14 trauma [15][16][17] and obstetric fields, 18 have not demonstrated the presence of the July effect. However, several of these studies were limited by their single-centre nature and their focus on a single patient group.…”
mentioning
confidence: 99%